Epistemologi Mistisisme Perspektif Bertrand Russell dan Mulyadhi Kartanegara - Classix, Hatta; Kurniawan, Wawan (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2025)
This study is motivated by the tension between modern rationalism, which remains critical of mysticism, and religious thought that integrates spiritual experience into the framework of epistemology. The research aims to comparatively examine the epistemology of mysticism in Bertrand Russell and Mulyadhi Kartanegara, focusing on the definition, the way mystical experience is attained, its epistemological status, and its ontological implications. Employing a qualitative method through library research and comparative analysis, the study finds that Russell rejected the epistemic validity of mysticism as it contradicted the principles of logic and empirical science, whereas Kartanegara regarded mystical experience as an integral dimension of human intellect that complements reason and the senses. The study concludes that their fundamental difference lies in the acceptance of non-empirical dimensions, highlighting the importance of fostering dialogue between critical rationality and spirituality to achieve a more holistic understanding of reality.